Incidence (2008-2015) of post-traumatic headaches in United States military personnel. (21st March 2021) - Nabity, Paul S.; Moore, Brian A.; Peterson, Alan L.; McGeary, Donald D.
ABSTRACT: Objective : To conduct a descriptive transversal study to evaluate the incidence and demographic characteristics of post-traumatic headache using data from the Defense Medical Epidemiology Database. Methods : A retrospective cohort study was conducted of data from 2008 to 2015 based on the International Classification of Diseases codes for both acute and chronic post-traumatic headache. Results : A total of 17, 010 new cases of post-traumatic headaches were diagnosed among active duty military personnel. Reported incidence rates of post-traumatic headaches in the military increased 29-fold over the timeframe analyzed. Males enlisted in the Army were more likely to be diagnosed with post-traumatic headaches than females (O/E = 0.76), other branches, and officers. Conclusion : Findings of this study indicate that there is a significant incidence of post-traumatic headaches in the U.S. military. However, the incidence rates of post-traumatic headaches in the military are much lower than what was expected considering the number of traumatic brain injuries in the United States military reported by the Department of Defense for the same period. Additional research is needed to further evaluate these differences and the impact of PTHs on military personnel.